Three-dimensional spheroid culture targeting versatile tissue bioassays using a PDMS-based hanging drop array - Ching-Te Kuo (Nature Portfolio, 2017)
Abstract Biomaterial-based tissue culture platforms have emerged as useful tools to mimic in vivo physiological microenvironments in experimental cell biology and clinical studies. We describe herein a three-dimensional (3D) tissue culture platform using a polydimethylsiloxane (PDMS)-based hanging drop array (PDMS-HDA) methodology. Multicellular spheroids can be achieved within 24 h and further boosted by incorporating collagen fibrils in PDMS-HDA. In addition, the spheroids generated from different human tumor cells exhibited distinct sensitivities toward drug chemotherapeutic agents and radiation as compared with two-dimensional (2D) cultures that often lack in vivo-like biological insights. We also demonstrated that multicellular spheroids may enable key hallmarks of tissue-based bioassays, including drug screening, tumor dissemination, cell co-culture, and tumor invasion. Taken together, these results offer new opportunities not only to achieve the active control of 3D multicellular spheroids on demand, but also to establish a rapid and cost-effective platform to study anti-cancer therapeutics and tumor microenvironments.